A new closed form for optimal co-channel deployment of femto cells in Rayleigh fading environment - Pongsatorn Sedtheetorn (2018)
In this paper, theoretical analysis on co-channel deployment of a femto cell network in Rayleigh fading is addressed. It is well known that co-channel deployment is useful in terms of capacity improvement but it impacts on the signal degradation. Therefore, the major challenge is on the tradeoff between the capacity enhancement and signal deterioration. Here, a new closed form is formulated to evaluate the maximum number of co-channel femto cells while the signal quality, represented by the outage probability, is kept guaranteed. This benefits us to determine the optimized number of co-channel femto cells at any given value of the signal quality requirements. © 2014 IEEE.